2019
DOI: 10.1186/s12879-019-4261-3
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of serum soluble ST2 in clinical relapse after stopping long-term Nucleos(t)ide analogue therapy for chronic hepatitis B

Abstract: Background The virological or clinical relapse is common in chronic hepatitis B (CHB) patients after stopping long-term nucleos(t)ide analogue (NA) therapy. Soluble growth stimulation expressed gene 2 (sST2), one of the Toll-like/interleukin-1 receptor members, is involved in a variety of inflammatory processes and immune responses. However, the expression and function of serum sST2 in CHB patients after stopping NA treatment remains unknown. Methods A total of 91 non-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Male gender was associated with off-NAs VR only in one study [24]. In addition, older age was associated with off-NAs VR in seven studies (all with both HBeAg-positive and HBeAg-negative patients) [19,23,33,[39][40][41]43], and two of these studies found that higher rates of off-NAs VR in patients >35 years old than patients ≤35 years old [33,44]. They did not found off-NAs VR was association with alcohol consumption in one [36], diabetes and hypertension in one [28], and body mass index (BMI) in two studies [29,36].…”
Section: Factors Associated With Vr After Nas Cessationmentioning
confidence: 95%
See 4 more Smart Citations
“…Male gender was associated with off-NAs VR only in one study [24]. In addition, older age was associated with off-NAs VR in seven studies (all with both HBeAg-positive and HBeAg-negative patients) [19,23,33,[39][40][41]43], and two of these studies found that higher rates of off-NAs VR in patients >35 years old than patients ≤35 years old [33,44]. They did not found off-NAs VR was association with alcohol consumption in one [36], diabetes and hypertension in one [28], and body mass index (BMI) in two studies [29,36].…”
Section: Factors Associated With Vr After Nas Cessationmentioning
confidence: 95%
“…The rate of VR after NAs cessation was not related to the type of NAs in six studies using rst-line (tenofovir or entecavir) and second-line NAs (adefovir, lamivudine or telbivudine) involving 683 patients (330 HBeAgpositive, 353 HBeAg-negative) [33,36,37,39,40,44]. Whereas, the rate of VR was higher in 22 tenofovir-treated than 113 entecavir-treated HBeAg-negative CHB patients in one study [41].…”
Section: Factors Associated With Vr After Nas Cessationmentioning
confidence: 97%
See 3 more Smart Citations